Two Modified QN-Algorithms for Solving Unconstrained Optimization Problems - Abbas Al-Bayati; Basim Hassan (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper presents two modified Quasi-Newton algorithms which are designed for solving nonlinear unconstrained optimization problems. These algorithms are based on  different techniques namely: Quasi-Newton conditions on quadratic and non-quadratic objective functions. Experimental results indicate that the new proposed algorithms are more efficient than the Yuan and Biggs- algorithms.